2023
DOI: 10.1007/s10648-023-09729-1
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Effects of the COVID-19 Pandemic on Children’s Writing: a Follow-up Replication Study

Abstract: The COVID-19 pandemic and the move by governments worldwide to cancel in-class instruction and move to emergency remote instruction in March and April of 2020 created an unprecedented disruption in children’s education. As the COVID-19 pandemic took form and continued to impact education in the following 2020/2021 academic year, multiple concerns were raised about possible negative effects on students’ learning. The current longitudinal replication study examined this proposition for second-grade students in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 35 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…However, we were unable to obtain specific data on how the pandemic affected schools in the current investigation. One study that focused on the writing proficiency of second-grade students found no significant effects of measures taken to mitigate the spread of the pandemic (Skar et al, 2023 ). Another investigation examining national test results in English, reading, and mathematics revealed either small or positive effects of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…However, we were unable to obtain specific data on how the pandemic affected schools in the current investigation. One study that focused on the writing proficiency of second-grade students found no significant effects of measures taken to mitigate the spread of the pandemic (Skar et al, 2023 ). Another investigation examining national test results in English, reading, and mathematics revealed either small or positive effects of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…That is no longer a dubious claim. The effects of the COVID-19 pandemic alone have forced us to face undesirable realities and overwhelming challenges (Di Pietro, 2023;Hass et al, 2023;Okagbue et al, 2023;Skar et al, 2023). These challenges appear worldwide, albeit in different forms.…”
Section: How Should We Critically Look At and Meet Desired Outcomes A...mentioning
confidence: 99%